PERAN ORANG TUA DALAM MEMBINA KECERDASAN SPIRITUAL - Ahmad Rifai (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2018)
Family is the first and main place for the growth and development of children. If the condition in the family is good and happy so that the children will grow well. To develop SQ in the family, parents can develop by: duty, care, knowledge, personal change, brotherhood and dedicated leadership. The first place to grow spiritual quotient or spiritual intelligence is family. The children that are grown in high spiritual quotient family environment will be high spiritual quotient people also.